2010
DOI: 10.1111/j.1540-4609.2010.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Instruction and Learning Outcomes: A Theoretical Analysis of Two Approaches in an Introductory Information Technology Course*

Abstract: In introductory information technology (IT) courses, communicating technical concepts so that they can be comprehended by all students, technical and nontechnical, has been a concern. Another challenge in such courses is to teach the real-world applicability of technical concepts. In this conceptual article, we focus on a relatively unexplored issue in IT education-which instructional method is more effective in improving the learning outcomes of all students taking introductory IT courses. In doing so, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Deal (2007) noted that lecture Webcasts can improve students' educational experiences by reducing stress and providing an additional study resource. Pridmore, Bradley, and Mehta (2010) found that students perceive that the use of two instructional methodologies (lecture and multimedia case studies) combined is more effective than the use of a single methodology. Ahmed (2010) studied hybrid e-learning acceptance by learners using three critical success factors: instructor' characteristics, information technology infrastructure, and organizational and technical support.…”
Section: Improve (I): Select Course Of Actionmentioning
confidence: 96%
“…Deal (2007) noted that lecture Webcasts can improve students' educational experiences by reducing stress and providing an additional study resource. Pridmore, Bradley, and Mehta (2010) found that students perceive that the use of two instructional methodologies (lecture and multimedia case studies) combined is more effective than the use of a single methodology. Ahmed (2010) studied hybrid e-learning acceptance by learners using three critical success factors: instructor' characteristics, information technology infrastructure, and organizational and technical support.…”
Section: Improve (I): Select Course Of Actionmentioning
confidence: 96%
“…Active learning contrasts with passive learning, which typically involves traditional lecture formats or reading assignments. Passive learning continues to be a mainstay in many Introduction to Information System (IIS) classes (Pridmore, Bradley, & Mehta, 2010). Traditional lecture format often challenges students' attention span, resulting in a rapid drop-off in the retention of class topics (Hartley & Davies, 1978;Wankat, 2002).…”
Section: Editor: Lorraine Staehrmentioning
confidence: 99%
“…Identifying and assessing learning outcomes is very important (Duke, 2002; Pridmore, Bradley, & Mehta, 2010). Learning outcomes has been measured through theoretical models such as TAM (Landry, Griffeth, & Hartman, 2006) and E‐Learning success model (DeLone and McLean, 2003).…”
Section: Framework and Hypotheses Buildingmentioning
confidence: 99%